KONSEP PENDIDIKAN AKHLAK MENURUT IBNU MISKAWAIH - Parlaungan Lubis, Mhd Fauzil Adim Nasution, Tuti Alawiyah, (Fakultas Agama Islam, 2022)
Moral is a condition in a person's soul, which is the source of his actions, which are alternative (good or bad) in accordance with the influence of the education given to him. If this soul is educated to praise glory and truth, it will easily be born of good deeds and it is not difficult to practice good morals (akhlakul karimah). On the contrary, on the contrary, the soul is neglected, not properly educated so that it loves and loves, it will emerge from it despicable and flawed words, which are called bad morals (akhlakul madzmumah). Therefore, Islam has good morals and teaches Muslims to build morals and instill them in their souls. The research in this thesis refers to the concepts described by Ibn Miskawaih in several of his essays. By taking the title Ibn Miskawaih's Moral Education Concept. The objectives of this research are: To know the concept of education of Ibn Miskawaih Morals in order to maintain human dignity and instill good morals for students in schools. This type of research is library research using a descriptive qualitative approach. That is research that describes the properties or characteristics of individuals, circumstances, symptoms, or certain groups. With the descriptive method of content analysis, namely the method by analyzing the content and describing the object under study through the sources related in this study. The results of this study are: Ibn Miskawaih gives an understanding of the middle or middle way that must be achieved by each individual in order to maintain dignity and achieve moral perfection. He emphasized that every virtue has two sides. The middle side is commendable and the extreme side is reprehensible. Such as should not think wrong and should not be excessive but must be wise. You can't be a coward, and should not be reckless, the middle way is courage. You can't be stingy, but you can't be wasteful either. The middle way is not to be expounded and expounded, the middle way is fair And Ibn Miskawath gives a special position to the teacher, the teacher is considered to be more instrumental in educating his psyche in order to achieve true happiness Ibn Miskawaih aims for every teacher / educator, regardless of the material in the field of knowledge he nurtures must be directed to create noble character for himself and his students Not only teach or deliver the subject matter he teaches but also must insert ethical values in the lessons taught.